Pengaruh work-life balance terhadap job performance dengan job satisfaction sebagai variabel interveing - Dalila, Arini; Kholidi Hadi, Hafid (Jurnal Ilmu Manajemen, 2024)
This research aims to test and analyse the effect of work-life balance on job performance with job satisfaction as an intervening variable at health agency X in Bangkalan Regency, East Java. This research is a type of quantitative research. Sampling used a saturated sampling technique with 57 medical employee respondents. The statistical analysis used in this research applies SEM-PLS with the help of SmartPLS 3.2.9 software. The results of this research prove that work-life balance has a positive and significant effect on job performance, work-life balance has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on job performance, and job satisfaction mediates the effect of work-life balance on job performance. Implications based on research show that health agency X needs to pay attention to employee time management to create a good work-life balance. Apart from that, health agency X needs to help employees increase their level of job satisfaction so that it will have an impact on their resulting performance.